Perencanaan konektivitas rute pengangkutan umum - Antonius Romi Andika Pradipta; Bella Aresta Kadang; Cornelius Angga Widiprasetyo; Hadisantono; Parama Kartika Dewa (Universitas Atma Jaya Yogyakarta, 2023)
[Title: Optimization of Public Transport Route Connectivity with Route Finder] According to data.jakarta.go.id alerts, in 2020 the number of public transportation in Jakarta is dominated by microbus type cars with a total of 2,605 units. Followed by city transportation (angkot) KWK (Wahana Kalpika Cooperative) totaling 2,042 units, Transjakarta 1,296 units, minibus replacement transportation (APB) 577 units, and Metromini buses 7 units. However, this public transportation is not the main option for most Jakarta residents because it is considered inefficient in terms of time and inflexible mobility. Therefore, in order to increase public interest in using public transportation, a system is needed to manage public transportation such as Transjakarta, MRT and KRL which can provide information regarding schedules and costs that must be incurred and can connect existing modes of public transportation by providing multi-transport options based on the user's destination route so that public transport functions become more optimal.